Students Conflict Resolution Skills through Social Problem-Solving and Social Inquiry Models in Terms of Organization Experience - Dianasari; Bunyamin Maftuh; Ernawulan Syaodih; Sapriya; Ma Arsenia Gomez (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
This mixed-method research aims to determine the interaction between the learning process using the two models and university students organizational experience on conflict resolution skills (Factor 1), and to determine the difference in influence between organization experience called BSLT (Factor 2). The research by using sequential explanation population was all PGSD university students at Muhammadiyah University of Cirebon, in 30 university students. The sampling technique uses purposive sampling. The research instrument uses test questions and interview guidelines. The results of this study found that the influence of Factor 1 had no effect. However, based on the results of Factor 2, it shows that there is an influence between the conflict resolution skills of university students who have taken BSLT and those who have never taken BSLT. This shows that the experience of taking BSLT has an effect on university students' conflict resolution abilities, compared to just using the learning model. The impact of university students mastering good conflict resolution skills is the creation of a positive climate in the organizational and campus environment. As well as university students' agility in eliminating potential conflicts that develop, so that they can be resolved immediately. Keywords:  Conflict Resolution, Human Rights, Social Problem Solving, Social Inquiry